2015
DOI: 10.1021/jp512621r
|View full text |Cite
|
Sign up to set email alerts
|

Pure and Oxidized Ag Substrate Influence on the Phase Transformation and Semiconducting Behaviors of Layered ZnO: A First-Principles Study

Abstract: Graphitic-like ZnO layers have been experimentally synthesized on metal substrates over the past few years. Nevertheless, the impact of metal substrates on the structural and electric properties of ZnO is still unclear. Utilizing first-principle calculations with van der Waals correction, we found that the phase transformation from graphitic-like to wurtzite structure occurs when the thickness of freestanding ZnO exceeds seven layers. With the presence of pure Ag(111) substrate, the critical transformation thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…The polar wurtzite ZnO(0001)-Zn and ZnO(0001̅)-O surfaces are unstable, causing reconstructions that stabilize these surfaces. , However, in the ultrathin ZnO regime, a different stabilization mechanism is at work; where depolarization takes place via the formation of the unreconstructed planar sheets (Figure b). , Structurally, the bonding configuration of the Zn and O atoms in the ZnO layers changes from sp 3 tetrahedral in the wurtzite structure to sp 2 trigonal coordination in the planar structure. For free-standing ZnO, the critical thickness up to which the planar structure is stable was predicted computationally to be ∼8 layers, , while in the case of ZnO layers supported on a Ag(111) surface, the planar structure was calculated to be stable up to a bilayer . Experimentally, it was found that the ZnO layers on Ag(111) and Pd(111) adopt bulk-like structures at a thickness of 4 layers. , …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The polar wurtzite ZnO(0001)-Zn and ZnO(0001̅)-O surfaces are unstable, causing reconstructions that stabilize these surfaces. , However, in the ultrathin ZnO regime, a different stabilization mechanism is at work; where depolarization takes place via the formation of the unreconstructed planar sheets (Figure b). , Structurally, the bonding configuration of the Zn and O atoms in the ZnO layers changes from sp 3 tetrahedral in the wurtzite structure to sp 2 trigonal coordination in the planar structure. For free-standing ZnO, the critical thickness up to which the planar structure is stable was predicted computationally to be ∼8 layers, , while in the case of ZnO layers supported on a Ag(111) surface, the planar structure was calculated to be stable up to a bilayer . Experimentally, it was found that the ZnO layers on Ag(111) and Pd(111) adopt bulk-like structures at a thickness of 4 layers. , …”
mentioning
confidence: 99%
“…For free-standing ZnO, the critical thickness up to which the planar structure is stable was predicted computationally to be ∼8 layers, 15,17 while in the case of ZnO layers supported on a Ag(111) surface, the planar structure was calculated to be stable up to a bilayer. 18 Experimentally, it was found that the ZnO layers on Ag(111) and Pd(111) adopt bulk-like structures at a thickness of 4 layers. 16,19 A material's band gap is another important property which can impact its application in photovoltaics, sensing, and photocatalysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the calculated formation energies of nL ZnO are listed in Table 1 as inversely related to the number of layers. Many studies have successfully synthesized monolayer or few-layer ZnO [21,27]. therefore, these formation energies might indicate that several layers of ZnO were more stable and more comfortable to synthesize than monolayer ZnO.…”
Section: Geometric Structures and Electronic Properties Of Multilayermentioning
confidence: 99%
“…In the case of ZnO, for instance, due to surface depolarization, ZnO films that are only a few atomic layers thick favor a stable graphite-like multilayer structure. Furthermore, when the number of layers increases, ZnO films begin transforming into the bulk structure at a certain critical thickness [21][22][23][24][25]. Theoretically, some previous first-principles calculation studies predicted the existence of graphite-like multilayer ZnO [9,26].…”
Section: Introductionmentioning
confidence: 96%